Faktor-Faktor Yang Memengaruhi Minat Mahasiswa Akuntansi Memperoleh Sertifikasi Chartered Accountant - Anak Agung Ayu Indah Puspita Dewi; Komang Ayu Krisnadewi (Serat Acitya, 2023)
This research aims to examine the influence of factors that influence accounting students' interest in obtaining Chartered Accountant (CA) certification. Behavioral Decision Theory based on the belief, preference and constraint model is used to explain the influence of capabilities, environmental factor, socio-cultural factor, preference, and constraint faced on accounting students' interest in obtaining CA certification. Gender and GPA variables are used as control variables. The population in this research is active Bachelor of Accounting students who come from state/private universities in Bali, Indonesia. The sample determination method uses a nonprobability sampling method with a purposive sampling technique. Data collection in this research used a survey method by distributing questionnaires with a sample size of 86 respondents. The data analysis techniques used are logistic regression analysis and multiple linear regression analysis. The results of data analysis show that capabilities have a positive effect on accounting students' interest in obtaining CA certification.